Glycosylphosphatidylinositol-anchored proteins in Fusarium graminearum: inventory, variability, and virulence. - William R Rittenour; Steven D Harris (PLoS ONE, 2013)
The contribution of cell surface proteins to plant pathogenicity of fungi is not well understood. As such, the objective of this study was to investigate the functions and importance of glycosylphosphatidylinositol-anchored proteins (GPI-APs) in the wheat pathogen F. graminearum. GPI-APs are surface proteins that are attached to either the membrane or cell wall. In order to simultaneously disrupt several GPI-APs, a phosphoethanolamine transferase-encoding gene gpi7 was deleted and the resultant mutant characterized in terms of growth, development, and virulence. The Δgpi7 mutants exhibited slower radial growth rates and aberrantly shaped macroconidia. Furthermore, virulence tests and microscopic analyses indicated that Gpi7 is required for ramification of the fungus throughout the rachis of wheat heads. In parallel, bioinformatics tools were utilized to predict and inventory GPI-APs within the proteome of F. graminearum. Two of the genes identified in this screen (FGSG_01588 and FGSG_08844) displayed isolate-specific length variability as observed for other fungal cell wall adhesion genes. Nevertheless, deletion of these genes failed to reveal obvious defects in growth, development, or virulence. This research demonstrates the global importance of GPI-APs to in planta proliferation in F. graminearum, and also highlights the potential of individual GPI-APs as diagnostic markers.